(untitled) (Dissertare, 2016)
This paper aims to describe the emerging worldview features (indigenous and nonindigenous) from La Vega de Los Gayones of Kumunibare community at Cují-Tamaca parish of Lara State. These features were presented at the Doctoral Thesis called Senses and Meanings of Indigenous Idiomatic Revitalization (Gayón Language) from the Social Construction. The central concern of the thesis mentioned was to rescue ancestral knowledge and reveal some distinguished aspects of the people who provided information through conversations and personal contact. It is also important to note that this is a qualitative study with an emerging reality and a subjective interpretation that encompasses the triad: actors, theory and researcher based on the phenomenological hermeneutical method, which allows a true reflection of contextual aspects. The methodology used was the observation and depth interview for the informative contribution. The interpretation of the data was performed through techniques to analyze the discourse of the social actors. It should be noted that in order to validate the worldview of the indigenous, it was taken into account the Intercultural Bilingual Education as specific arrangement at all levels and modalities of the educational system for indigenous peoples, in order to promote intercultural situations and fulfil individual and collective needs of these communities.